Antibacterial Activity of Ethanol Extract Combination of Binahong and Basil Leaves to The Growth of Escherichia coli - Amaliah, Afrida; Lisdiana, Lisa (LenteraBio : Berkala Ilmiah Biologi, 2022)
Diarrhea is a disease caused by an infection in the digestive tract. The bacteria that causes infection on the digestive tract is Escherichia coli. The use of antibiotics to treat various diseases has the potential to increase bacterial resistance. Binahong and basil leaves have the potential to be natural alternative treatments because of their secondary metabolites content. This study aims to determine the antibacterial activity of ethanol extract of binahong and basil leaves, as well as its optimal ethanol extract combination to inhibit the growth of E.coli. The well-diffusion method used in this study was designed using a completely randomized design (CRD). Preliminary studies were carried out to determine the minimum inhibitory concentration (MIC) of each extract followed by antibacterial activity analysis of the extract combination, including the ratio of extract combinations 1:3, 2:2, 3:1, antibiotic Ciprofloxacin (positive control) and DMSO 10% (negative control). The test results were analyzed by Kolmogorov-Smirnov test and ANOVA followed by Duncan's test which showed that the ethanol extract combination of binahong and basil leaves was able to inhibit the growth of E. coli. The combination treatment of extracts with a ratio of 1:3 resulted in the largest inhibition zone, which was 1.96 ± 0.23 cm. In the future, the extract combination of binahong and basil leaves can be used as the main material for medicine in the pharmaceutical industry.